Central Poststroke Pain: An Abstruse Outcome. (2008) - Henry, James L; Lalloo, Chitra; Yashpal, Kiran
Abstract : Central poststroke pain (CPSP), formerly known as thalamic pain syndrome of Déjerine and Roussy, is a central neuropathic pain occurring in patients affected by stroke. It is one manifestation of central pain, which is broadly defined as central neuropathic pain caused by lesions or dysfunction in the central nervous system. Thalamic pain was first described 100 years ago by Déjerine and Roussy and has been described as "among the most spectacular, distressing, and intractable of pain syndromes". CPSP is characterized by constant or intermittent pain and is associated with sensory abnormalities, particularly of thermal sensation. While the pain is frequently described as burning, scalding, or burning and freezing, other symptoms are usually vague and hard to characterize, making an early diagnosis particularly difficult. In fact, those who develop CPSP may no longer be under the care of health care professionals when their symptoms begin to manifest, resulting in misdiagnosis or a significant delay before treatment begins. Diagnosis is further complicated by cognitive and speech limitations that may occur following stroke, as well as by depression, anxiety and sleep disturbances. Patients may also exhibit spontaneous dysesthesia and the stimulus-evoked sensory disturbances of dysesthesia, allodynia and hyperalgesia. The present study offers a historical reference point for future clinical and basic research into this elusive type of debilitating pain.